Pengaruh Self-Efficacy, Person-Job Fit, dan Job Characteristic terhadap Komitmen Organisasi pada Karyawan PT XYZ - Mardiyah, Arrifah Ainul; Karyono, Karyono (Lembaga Yasin AlSys, 2024)
This research was conducted on employees of PT The aim of this research is to find out whether organizational commitment is influenced by self-efficacy, person-job fit, and job characteristics. The analytical method in this research uses multiple linear regression analysis using IBM SPSS 25. Data was collected using questionnaire results from 36 employees. The results of the research show that: (1) Self-efficacy, person-job fit, and job characteristics together have a positive and significant effect on organizational commitment; (2) Self-efficacy has a positive and insignificant effect on organizational commitment; (3) Person-job fit has a positive and significant effect on organizational commitment; and (4) Job characteristics have a positive and significant effect on organizational commitment.